2015 IEEE Asian Solid-State Circuits Conference (A-Sscc) 2015
DOI: 10.1109/asscc.2015.7387484
|View full text |Cite
|
Sign up to set email alerts
|

A 1V 9pA analog front end with compressed sensing for electrocardiogram monitoring

Abstract: An analog front-end (AFE) for Electrocardiogram (ECG) monitoring with built-in compressed sensing (CS) is presented. The CS is incorporated into an array of incremental ADCs, and the power overhead is minimized through segmented CS and dynamic bias control. A decompression technique is also presented to enhance the effective resolution of CS by 1b without degrading the compression ratio (CR). This AFE, fabricated in a 0.11μm CMOS process, compresses data by 78/56% with a 7/8b resolution, and consumes only 9μA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…The energy required in both the cases are theoretically calculated by considering the total number of microcontroller unit (MCU) cycles and transmission bitrate required by microcontroller used. Similar calculation is done by Poian et al [230] and Kuo et al [231] for ECG signal and showed the total energy saving evaluation.…”
Section: Energy Consumption Evaluationsupporting
confidence: 63%
“…The energy required in both the cases are theoretically calculated by considering the total number of microcontroller unit (MCU) cycles and transmission bitrate required by microcontroller used. Similar calculation is done by Poian et al [230] and Kuo et al [231] for ECG signal and showed the total energy saving evaluation.…”
Section: Energy Consumption Evaluationsupporting
confidence: 63%
“…The energy required in both the cases are theoretically calculated by considering the total number of microcontroller unit (MCU) cycles and transmission bitrate required by microcontroller used. Similar calculation is done by Poian et al [230] and Kuo et al [231] for ECG signal and showed the total energy saving evaluation.…”
Section: Energy Consumption Evaluationsupporting
confidence: 63%